Use of social media towards depression and achievement motivation among university students - Julius, Stepheny; Mohamad Yusop, Yusni; Zainudin, Zaida Nor; Wan Othman, Wan Norhayati; Sumari, Melati; Engku Kamarudin, Engku Mardiah; Abdul Ghafar, Nurul Nadia (Karadeniz Technical University, 2021)
This study analyses the relationship of the use of social media towards depression and achievement motivation among university’s students. There are n = 174 respondents of degree student participate in this studyby using cluster sampling method (age range = 19-23). Descriptive analysis and Pearson correlation is used to identify the level and relationship of Social Media Use, Depression and Achievement Motivation respectively. The results showed level of social media use and depression level is mild while achievement motivation is moderate. The relationship between the use of social media and depression is a moderate positive correlation. Besides, the relationship between the use of social media and achievement motivation is a moderate positive correlation. Both correlation is significant. As social media has significant relationship with depression and motivation achievement, the use of social media wisely is highly recommended in order to benefit the usage and prevent from any social media vices.